Prevalence of Clostridium difficile infection among the patients attending a tertiary care teaching hospital - Lavanya Segar; Joshy M Easow; Sreenivasan Srirangaraj; Mohammad Hanifah; Noyal M Joseph; K S Seetha (Wolters Kluwer Medknow Publications, 2017)
Background: Clostridium difficile, a most important nosocomial enteric pathogen, is recognized globally as responsible for antibiotic-associated diarrhea and colitis. It is associated with considerable morbidity and mortality due to widespread use of antibiotics. Aims: The study was done to determine the prevalence of C. difficile infection (CDI) among the patients attending a tertiary care teaching hospital in Puducherry. Settings and Design: We performed a prospective cohort study in Mahatma Gandhi Medical College and Research Institute. Materials and Methods: Around 150 patients were evaluated along with the patient details. C. difficile toxin detection was done as per the standard algorithm using the C. Diff Quik Chek Complete® assay (TECHLAB, Blacksburg, VA, USA). Statistical Analysis Used: Analysis was done using statistics software (SPSS 16.0, SPSS Inc., Chicago, IL, USA). Results: The prevalence of CDI was found to be 4%. More toxin-positive cases were between 50 and 60 years of age, and there was no difference in gender. Intensive Care Unit showed more toxin-positive cases; however, there was no significant association between the occurrence of CDI and the primary diagnosis of the patients. Conclusions: The prevalence of CDI in our hospital was found to be 4%, which was relatively lower compared to other Indian studies. However, awareness of the risk factors may assist in identifying patients at higher risk for CDI, guide implementation of appropriate preventive measures, and modulate potential intervention measure during management.